A Region of Plasmodium falciparum Antigen Pfs25 That Is the Target of Highly Potent Transmission-Blocking Antibodies - Stowers, Anthony W. (American Society for Microbiology, 2000)
Each of the four epidermal growth factor (EGF)-like domains of the Plasmodium falciparum sexual-stage antigen Pfs25 has been individually expressed as a yeast-secreted recombinant protein (yEGF1 through yEGF4). All four are recognized by the immune sera of animals and humans vaccinated with TBV25H (the corresponding yeast-secreted full-length recombinant form of Pfs25), with antibody titers to yEGF1 and yEGF2 weakly correlating with the ability of the sera to block the transmission of parasites to the mosquito host. All four proteins are poorly immunogenic in mice vaccinated with aluminum hydroxide-absorbed formulations. However, all four successfully primed the mice to mount an effective secondary antibody response after a single boost with TBV25H. Sera from mice vaccinated with yEGF2-TBV25H completely block the development of oocysts in mosquito midguts in membrane-feeding assays. Further, of the four proteins, only the depletion of antibodies to yEGF2 from the sera of rabbits vaccinated with TBV25H consistently abolished the ability of those sera to block oocyst development. Thus, antibodies to the second EGF-like domain of Pfs25 appear to mediate a very potent blocking activity, even at low titers. Vaccination strategies that target antibody response towards this domain may improve the efficacy of future transmission-blocking vaccines.